Manajemen Wakaf Pondok Modern Darussalam Gontor Kampus 7 Dalam Pengembangan Pondok Pesantren Di Kalianda - Mahendra, Mahendra; Hasan, Yetri; Thahir, Andi; Ayu, Sovia Mas; Junaidah, Junaidah (Universitas Islam Negeri Raden Intan Lampung, 2022)
This study aimed to know the waqf management and asset empowerment of waqf boarding school in Pondok Modern Darussalam Gontor Campus 7 Kalianda. Also, it aimed to know the main obstacles in the implementation of management functions in the management of waqf boarding school in Pondok Modern Darussalam Gontor Campus 7 Kalianda. This research was qualitative research with descriptive approach based on case studies. The data weretaken from the leader of Pondok Modern Darussalam Gontor Campus 7, YPPWPM management, teachers and the management of Gontor organization. This study used observation, interviews and documentation as data collection tools. Then, the data that had been collected was analyzed with the stages of data reduction, data presentation and drawing conclusions. The results showed that the development of Pondok Modern Darussalam Gontor Campus 7 Kalianda could be separated from the role of waqf management, starting from the waqf of infrastructure facilities, waqf of business unit and waqf from the teachers in Gontor. They did not belong to individuals but to the people, which has been donated to the boarding school. Therefore, Gontor had a rapid development because of its waqf.